Application and effectiveness of blended learning in medical imaging via the technology acceptance model - Xiaofen Sun; Jianghua Wan; Zhiqun Li; Rong Tu; Juan Lin; Xiaohua Li; Jianqiang Chen (BMC Medical Education)
Abstract Blended learning, which integrates online education with face-to-face instruction, is becoming an increasingly vital component of higher education. While there is an extensive research on blended learning, studies specifically examining student perceptions in the field of medical imaging are limited. This study investigates the satisfaction and behavioral intentions of students enrolled in a blended "Medical Imaging" course at Hainan Medical University. We employed a quantitative research approach, using a modified Technology Acceptance Model (TAM) questionnaire to fit the specific context of blended learning. Data were collected from 145 valid responses and analyzed using SPSS 26 and Smart-PLS 3.3.3. The findings reveal that blended learning positively impacts student satisfaction and engagement, underscoring its value in higher education. Additionally, the study supports the integration of the TAM to enhance the effectiveness of blended learning for students.